(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This scientific article is devoted to the study of the role of graphic clarity in Russian language lessons in the development of cognitive activity of primary schoolchildren. In the context of modern educational requirements, which emphasize the development of critical thinking, analytical skills and the ability to learn, it is important to determine what methods and means can contribute to effective teaching of the Russian language. The article discusses the theoretical basis of the influence of graphical clarity on learning, and also presents the results of an empirical study, including observations, surveys and data analysis. This article may be useful for both teachers and researchers interested in developing methods of teaching the Russian language in primary school.